Monitoring, Stimulation, Prevention and Remediation of Dense and Debris Flows IV 2012
DOI: 10.2495/deb120121
|View full text |Cite
|
Sign up to set email alerts
|

Riparian forest structure, vegetation cover and flood events in the Piave River

Abstract: Until very recently, rivers have been considered as the result of the interaction between water and sediments, thus simplifying this very complex system. In doing so, one important component was missed. This is vegetation, namely trees growing on banks, floodplains, and bars/islands. The pattern of riparian vegetation in gravel bed rivers depends on the climate, hydrological regime, floods, sediment transport and the morphological settings of the river. Also, the marked spatial variability of density, height, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…The median grain size varies between 20 and 50 mm. The Piave River features a complex pattern of vegetation distribution along the analysed study reach (Picco et al 2012a(Picco et al , 2012b(Picco et al , 2014, which is far more composite than those identified in less disturbed river systems (Hupp and Osterkamp, 1996;Gurnell and Petts, 2002;Tabacchi et al, 1998;Bendix and Hupp, 2000). …”
Section: Piave Rivermentioning
confidence: 99%
See 1 more Smart Citation
“…The median grain size varies between 20 and 50 mm. The Piave River features a complex pattern of vegetation distribution along the analysed study reach (Picco et al 2012a(Picco et al , 2012b(Picco et al , 2014, which is far more composite than those identified in less disturbed river systems (Hupp and Osterkamp, 1996;Gurnell and Petts, 2002;Tabacchi et al, 1998;Bendix and Hupp, 2000). …”
Section: Piave Rivermentioning
confidence: 99%
“…Kellerhals et al (1976) further discriminated between occasional, frequent, split and braided island patterns. The various aspects and characteristics of fluvial islands can also help to describe the river processes that happend in the past, some plant species require specific growth conditions, such as inundation duration, gradient, and particle size (Picco et al, 2012b) and that can help to determine the flow conditions in the area.…”
Section: Introductionmentioning
confidence: 99%
“…The analyzed study site presents a complex pattern of vegetation (Picco et al, 2012a). The narrowing and incision phase during the 20 th century (Comiti et al, 2011) has allowed the colonization of large areas by riparian forests (Picco et al, 2012a). Furthermore, the widening tendency shown during the last 20 years has led to the creation of pioneer islands through LW recruitment from bank erosions (Picco et al, 2012a).…”
Section: Study Site and Characteristicsmentioning
confidence: 99%
“…There are no tributaries within the study reach. The analyzed study site presents a complex pattern of vegetation (Picco et al, 2012a). The narrowing and incision phase during the 20 th century (Comiti et al, 2011) has allowed the colonization of large areas by riparian forests (Picco et al, 2012a).…”
Section: Study Site and Characteristicsmentioning
confidence: 99%
“…1) of the basin area disconnected from the lower river channel in terms of bedload transport, and between the 1960s and 1980s, there was intense sediment mining along the main channel [49]. As a result, the Piave River underwent narrowing and incision (see Table 1), and a progressive change from braided to a wandering/single-thread morphology, with the encroachment of riparian vegetation on the former active channel [7,44,47,55,59]. Widespread channel narrowing occurred in the range of 60-70% in the reach studied in this work [7].…”
mentioning
confidence: 99%